Discretion of Government Officials Detrimental to State Finances: The Intersection Between Administrative Illegality and Criminal Illegality - Rahman, Wahbi; Sudarsono, Sudarsono; Djatmika, Prija; Madjid, Abdul; Rehulina, Rehulina (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2024)
The regulation of the criminal accountability system for discretion that causes state losses is governed by Law Number 31 of 1999, as amended by Law Number 20 of 2001 on the Eradication of Corruption. This law includes the element of